2019
DOI: 10.1177/0309324719832735
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the damped dynamic behavior of a flexible pendulum

Abstract: The focus of this work is on the computational modeling of a pendulum made of a hyperelastic material and the corresponding experimental validation with the aim of contributing to the study of a material commonly used in seismic absorber devices. From the proposed dynamics experiment, the motion of the pendulum is recorded using a high-speed camera. The evolution of the pendulum’s positions is recovered using a capturing motion technique by tracking markers. The simulation of the problem is developed in the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Yuan [14] pointed out the limitation of the traditional viscous damping model and proposed a three-parameter damping model whose parameters were obtained experimentally to numerically analyse a four-bar elastic linkage mechanism. Ortega et al [17] indicated that with appropriate parameters, the Rayleigh damping model, which is a type of viscous damping model, in combination with Newmark numerical method can well capture the free vibration of a deformable physical pendulum. Salamon et al [10] investigated the capability of three viscous damping models, namely linear viscous damping model, squared velocity proportional damping model, and velocity and acceleration dependent damping model, in predicting the free vibration of physical pendulum systems.…”
Section: Introductionmentioning
confidence: 99%
“…Yuan [14] pointed out the limitation of the traditional viscous damping model and proposed a three-parameter damping model whose parameters were obtained experimentally to numerically analyse a four-bar elastic linkage mechanism. Ortega et al [17] indicated that with appropriate parameters, the Rayleigh damping model, which is a type of viscous damping model, in combination with Newmark numerical method can well capture the free vibration of a deformable physical pendulum. Salamon et al [10] investigated the capability of three viscous damping models, namely linear viscous damping model, squared velocity proportional damping model, and velocity and acceleration dependent damping model, in predicting the free vibration of physical pendulum systems.…”
Section: Introductionmentioning
confidence: 99%